Column absorption for reproducible cyclic separation in small scale ammonia synthesis. Issue 7 (28th February 2017) - Wagner, Kevin; Malmali, Mahdi; Smith, Collin; McCormick, Alon; Cussler, E. L.; Zhu, Ming; Seaton, Nicholas C. A.
Abstract : Ammonia is rapidly and reversibly absorbed on magnesium chloride supported on alumina. The absorption at ambient temperature is twice that on alumina alone, but much of the ammonia is still captured at 400°C, closer to the temperature of ammonia synthesis. Regeneration at 450°C is complete in 30 min; partial regeneration is faster, and is correlated with the temperature and the regeneration time. The supported absorbent column works for many cycles, reproducibly, because submicron‐sized MgCl2 crystals are trapped in similarly sized pores in the alumina itself, and the confinement prevents deterioration of the microstructure during absorption or regeneration. In contrast, while ammonia absorption into pure magnesium chloride is potentially much larger at equilibrium, the ammonia absorbs very slowly, and the chloride loses available capacity with use, probably because of fusing and deterioration of microstructure. A simplified model was constructed to simulate ammonia absorption into pure magnesium chloride and alumina‐supported magnesium chloride. © 2017 American Institute of Chemical Engineers AIChE J, 63: 3058–3068, 2017